Pregnancy in Women With a Fontan Circulation: A Systematic Review of the Literature. Issue 5 (May 2018) - Garcia Ropero, Alvaro; Baskar, Shankar; Roos Hesselink, Jolien W.; Girnius, Andrea; Zentner, Dominica; Swan, Lorna; Ladouceur, Magalie; Brown, Nicole; Veldtman, Gruschen R.
Abstract : Background: The Fontan operation has provided life-saving palliation and adult survival for individuals born with single ventricle physiology. Many now seek advice about safe pregnancy. Little data are, however, available, consisting mainly of anecdotal experience and small series. This article seeks to review the published literature and identify lessons learnt from this collective experience. Methods and Results: We conducted a systematic review to evaluate maternal and fetal outcomes of pregnancy in women with a Fontan circulation. Among 1150 studies that were screened, 6 studies had sufficient longitudinal data points to qualify for meaningful inclusion, yielding 255 pregnancies in 133 women after Fontan procedure resulting in 115 live births (45%; including reports from 1986 to 2015). There was a total of 137 pregnancy losses (69%), with 115 miscarriages (45%), 19 elective terminations of pregnancy (7%), 2 stillbirths (1%), and 1 ectopic pregnancy (1%).The most common cardiovascular adverse events were supraventricular arrhythmia affecting 8.4% (range, 3%–37%) and heart failure affecting 3.9% (range, 3%–11%) of pregnancies. These complications were successfully managed with conventional approaches. No maternal deaths were reported. Postpartum hemorrhage was the predominant obstetric complication affecting 14% of the patients. Most patients were on antiplatelet agents (27%) or anticoagulants (50%) whereas only a minority (11%) were on neither. Among the 115 live births, 68 were premature (59%), 17 were small for gestational age (20%), and neonatal death occurred in 6 patients (5%). Conclusions: The most commonly reported cardiovascular complications in patients with Fontan physiology–associated pregnancy were arrhythmia and heart failure. Miscarriages were highly prevalent as was prematurity and intrauterine growth restriction. Postpartum hemorrhage seems to be the most common obstetric complication. Large-scale data sets are needed to confirm these early observations and address the late sequelae of pregnancy in women with a Fontan circulation.